Strategi Pengembangan Usaha Keripik Pisang UD Al-Barokah Di Desa Bulangan Haji Kecamatan Pegantenan Kabupaten Pamekasan - Yanti Nurmalasari; Sustiyana Sustiyana; Taufikur Rahman (Universitas Islam Madura, 2021)
ABSTRACT This study aims to determine and analyze the development strategy of banana chips agroindustry UD. Al-barokah in Bulangan Haji Village is the most appropriate so that it is able to face the competition. Using SWOT analysis with IFAS and EFAS Matrix, it is possible to identify important factors from both the external and internal environment which are the strengths, weaknesses, opportunities and threats of the banana chips agroindustry. The location of the research was carried out purposively in Bulangan Haji Village, Pegantenan District, Pamekasan Regency. The analytical method used is descriptive quantitative analysis using the SWOT analysis method. SWOT analysis is the systematic identification of various factors to formulate the Banana Chips Agroindustry strategy. The results of the study indicate that a growth strategy or growth oriented strategy, this strategy indicates a strong agro-industry condition and is able to continue to develop by taking the opportunities or opportunities that exist.